Suicidality and self-harm in adolescents before and after the COVID-19 pandemic: a systematic review - Ferreira, Danilo Bastos Bispo; Santos, Renata Maria Silva; Machado, Maria Carolina Lobato; Rezende, Victhor Hugo Martins; de Marco, Patrícia Gazire; Romano-Silva, Marco Aurélio; de Miranda, Débora Marques (Frontiers in Psychiatry, 2025)
IntroductionAdolescent mental health, self-harm, and suicidality are critical concerns during this developmental stage, marked by intense physical, emotional, and social changes. The COVID - 19 pandemic has further intensified these vulnerabilities by disrupting daily routines, increasing social isolation, limiting access to mental health services, and exacerbating academic and emotional stressors.MethodsThis systematic review followed the PRISMA 2020 guidelines and employed the PECO strategy to identify relevant studies. A total of 55 quantitative studies published between 2010 and 2024 were included. These studies examined the prevalence and risk factors of self-harm and suicidal behaviors among adolescents aged 10 to 19 years, comparing findings from the pre-pandemic and pandemic periods. Psychosocial, economic, and cultural determinants were also evaluated.ResultsThe analysis revealed a consistent increase in self-harm and suicidality during the pandemic, with adolescent girls being disproportionately affected. Gender disparities were observed across diverse cultural contexts. Contributing factors included social isolation, excessive screen time, reduced access to education and healthcare, and increased family or financial stress. Cultural variability shaped both prevalence and clinical expression.DiscussionThese findings underscore the amplifying effect of the COVID - 19 pandemic on adolescent mental health vulnerabilities and highlight the need for culturally sensitive, gender-informed preventive strategies. Public policies should prioritize mental health support for youth and address systemic inequities to mitigate the psychological consequences of global crises. This review offers important insights into adolescent mental health in times of collective adversity.Clinical trial registrationPROSPERO https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024538641, identifier CRD42024538641.